The Impact of the Tumor Microenvironment on the Properties of Glioma Stem-Like Cells - Audia, Alessandra; Conroy, Siobhan; Glass, Rainer; Bhat, Krishna P. L. (Frontiers in Oncology, 2017)
Glioblastoma (GBM) is the most common and highly malignant primary brain tumor and patients affected with this disease exhibit a uniformly dismal prognosis. Glioma stem-like cells (GSCs) are a subset of cells within the bulk tumor that possess self-renewal and multi-lineage differentiation properties similar to somatic stem cells. These cells also are at the apex of the cellular hierarchy and cause tumor initiation and expansion after chemo-radiation. These traits make them an attractive target for therapeutic development. Because GSCs are dependent on the brain microenvironment for their growth, and because non-tumorigenic cell types in the microenviroment can influence GSC phenotypes and treatment response, a better understanding of these cell types is needed. In this review we provide a focused overview of the contributions from the microenvironment to GSC homing, maintenance, phenotypic plasticity, and tumor initiation. The interaction of GSCs with the vascular compartment, mesenchymal stem cells, immune system and normal brain cell types are discussed. Studies that provide mechanistic insight into each of these GSC-microenvironment interactions are warranted in the future.